Analysis of faster optical response in core/shell nanocrystals ferroelectric liquid crystal composite - Manohar, Rajiv; Singh, Dharmendra P; Pandey, Shivani; Srivastava, Atul (Photonics Letters of Poland, 2015)
<!– saved from url=(0022)http://internet.e-mail –> In the present study Cd1-xZnxS/ZnS core/shell nanocrystals dispersed ferroelectric liquid crystal (FLC) has been examined. The effect of NCs concentrations in FLC matrix for the electro-optical applications has been studied in the SmC* phase. A considerable variation in the parameters like tilt angle, spontaneous polarization, response time, anchoring energy and rotational viscosity has been observed for the composite system. Almost two fold faster optical response for the composite system is one of the promising results of the present study. Thus the present composite can be used for faster electro-optical devices. Full Text: PDF References J. Mirzaei, M. Urbanski, K. Yu, H. S. Kitzerow, T. Hegmann, "Nanocomposites of a nematic liquid crystal doped with magic-sized CdSe quantum dots", J. Mater Chem. 21, 12710 (2011). CrossRef S. Ghosh et al., "Effect of multiferroic BiFeO3 nanoparticles on electro-optical and dielectric properties of a partially fluorinated orthoconic antiferroelectric liquid crystal mixture", EPL 96, 47003 (2011). CrossRef A. Chaudhary, P. Malik, R. Mehra, K.K. Raina, "Electro-optic and dielectric studies of silica nanoparticle doped ferroelectric liquid crystal in SmC* phase", Phase Trans. 85, 244 (2012). CrossRef S. Pandey et al., "Cd1-xZnxS/ZnS core/shell quantum dot ferroelectric liquid crystal composite system: analysis of faster optical response and lower operating voltage", Liq. Cryst. 41, 1811 (2014). CrossRef D.P. Singh, S.K. Gupta, R. Manohar, "ZnO1-xSx Nanosphere in Ferroelectric Liquid Crystal Matrix: The Effect of Aggregation and Defects on the Dielectric and Electro-Optical Properties", Adv. Condens. Matt. Phys. 2013, 1 (2013). CrossRef W.K. Bae, M.K. Nam, K. Char, S. Lee, "Gram-Scale One-Pot Synthesis of Highly Luminescent Blue Emitting Cd1?xZnxS/ZnS Nanocrystals", Chem. Mater. 20, 5307 (2008). CrossRef S. Pandey et al., "Analysis of physical parameters and collective dielectric relaxations in core/shell quantum dot ferroelectric liquid crystal composite", J. Mol. Liq. 211, 157 (2015). CrossRef D.P. Singh, S.K. Gupta, R. Manohar, "Influence of CdSe quantum dot on molecular/ionic relaxation phenomenon and change in physical parameters of ferroelectric liquid crystal", Liq. Cryst. 42, 1159 (2015). CrossRef A.K. Srivastava, A.K. Misra, P.B. Chand, R. Manohar, J.P. Shukla, "Ferroelectric liquid crystals versus dyed ferroelectric liquid crystals in SmC* phase", Phys. Lett. A 371, 490 (2007). CrossRef Yu.P. Panarin, Yu.P. Kalmykov, S.T.M. Laughadha, H. Xu, J. K. Vij, "Dielectric response of surface stabilized ferroelectric liquid crystal cells", Phys. Rev. E 50, 4763 (1994). CrossRef R. Manohar, A.K. Srivastava, P.K. Tripathi, D.P. Singh, "Dielectric and electro-optical study of ZnO nano rods doped ferroelectric liquid crystals", J. Mater Sci. 46, 5969 (2011). CrossRef